Engineering young faculty's acceptance of real-time behavior measurement software - Marquez-Carpintero, Luis; Gomez-Donoso, Francisco; Cazorla, Miguel (Frontiers in Computer Science, 2025)
The integration of technology in education faces challenges like smartphone distractions. Educators' acceptance depends on perceived usefulness, ease of use, and technical support. Innovative methodologies, such as dynamic activity detection and wearable tech, improve classroom interaction and learning outcomes. However, no studies have focused on the acceptance of this software. This research examines young engineering professors' perceptions of advanced monitoring technologies for improving student attention and engagement based on their gestures, hypothesizing significant enhancements in teachers' performance according to Extended Technology Acceptance Model (TAM2). Data were collected from 10% of the young engineering faculty members (under 40 years old) at a Spanish university (107 individuals) through a structured questionnaire examining perceptions of usefulness, ease of use, and anxiety. Short training sessions proved critical for successful implementation, addressing financial, privacy, and technical challenges. Findings indicate positive acceptance, with ease of use influencing the intention to use and the image construct. Anxiety negatively impacts usage, underscoring the need to address it. Adequate technical support and continuous training are vital. The study reveals positive acceptance of real-time behavior measurement software among young engineering professors, highlighting the importance of training and addressing anxiety and institutional acceptance.